The disposition effect in securities trading: An experimental analysis - Martin Weber; Colin F. Camerer (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1991)
The "disposition effect" is the tendency to sell assets that have gained value ("winners") and keep assets that have lost value ("losers"). Disposition effects can be explained by two elements of prospect theory: The idea that people value gains and losses relative to the initial purchase price (a reference point), and the tendency to seek risks when faced with losses and avoid risks when faced with gains. In our experiments, subjects buy and sell shares in six risky assets. Asset prices fluctuate each period. As the disposition effect predicts, subjects sell winners and keep losers. When shares are automatically sold at the end of each period, the disposition effect is greatly reduced.
Keywords: 650